Efficacy of interventions to increase the uptake of chlamydia screening in primary care: a systematic review - Donovan Basil; Ward James; Poznanski Simone; Liu Bette; Ali Hammad; Guy Rebecca J; Kaldor John; Hocking Jane (BMC Infectious Diseases, 2011)
Abstract Background As most genital chlamydia infections are asymptomatic, screening is the main way to detect and cases for treatment. We undertook a systematic review of studies assessing the efficacy of interventions for increasing the uptake of chlamydia screening in primary care. Methods We reviewed studies which compared chlamydia screening in the presence and the absence of an intervention. The primary endpoints were screening rate or total tests. Results We identified 16 intervention strategies; 11 were randomised controlled trials and five observational studies, 10 targeted females only, five both males and females, and one males only. Of the 15 interventions among females, six were associated with significant increases in screening rates at the 0.05 level including a multifaceted quality improvement program that involved provision of a urine jar to patients at registration (44% in intervention clinics vs. 16% in the control clinic); linking screening to routine Pap smears (6.9% vs. 4.5%), computer alerts for doctors (12.2% vs. 10.6%); education workshops for clinic staff; internet-based continuing medical education (15.5% vs. 12.4%); and free sexual health consultations (16.8% vs. 13.2%). Of the six interventions targeting males, two found significant increases including the multifaceted quality improvement program in which urine jars were provided to patients at registration (45% vs. 15%); and the offering by doctors of a test to all presenting young male clients, prior to consultation (29 vs. 4%). Conclusions Interventions that promoted the universal offer of a chlamydia test in young people had the greatest impact on increasing screening in primary care.